2012
DOI: 10.3329/jsr.v4i2.8917
|View full text |Cite
|
Sign up to set email alerts
|

Mass Media Exposure and its Impact on Fertility: Current Scenario of Bangladesh

Abstract: On the way to reduce fertility rate of Bangladesh, mass media plays significant role to raise consciousness about the family planning program on general peoples. In this study the impact of mass media has been measured by the pattern of watching television, listening radio and reading newspaper. Using the proportional hazards model, the mass media exposure found to be a significant differential of fertility even after controlling the effects of contraception, place of residence, and mother's educational and em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(7 citation statements)
references
References 22 publications
(31 reference statements)
1
6
0
Order By: Relevance
“… 5 , 7 , 23 , 24 Previous studies reported that exposure to mass media exerts a strong positive impact in reducing teenage pregnancy as it contributes to creating awareness about the negative consequences of early childbearing and is very influential in motivating couples to adopt family-planning methods. 25 , 26 Our finding of a higher risk of pregnancy among uneducated women is consistent with studies conducted in LMICs. 7 , 22 , 24 , 27 , 28…”
Section: Discussionsupporting
confidence: 89%
“… 5 , 7 , 23 , 24 Previous studies reported that exposure to mass media exerts a strong positive impact in reducing teenage pregnancy as it contributes to creating awareness about the negative consequences of early childbearing and is very influential in motivating couples to adopt family-planning methods. 25 , 26 Our finding of a higher risk of pregnancy among uneducated women is consistent with studies conducted in LMICs. 7 , 22 , 24 , 27 , 28…”
Section: Discussionsupporting
confidence: 89%
“…The possible justification for desire to limit childbearing among media exposed women might be a large amount of information about fertility health, contraception use, and family planning programs has been provided by the public media. This can directly affect their desire to limit fertility [ 47 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Women from richer households are more likely to have better control over the decision to use contraception and are more aware of the consequences of early childbearing on their own and their children’s health ( 14 , 27 ). Household wealth could also reflect greater access to media as a tool for better knowledge and awareness including the decision to use contraceptives and reduce adolescent childbearing ( 13 , 33 , 34 ).…”
Section: Discussionmentioning
confidence: 99%